2020
DOI: 10.1002/acm2.13054
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of radiotherapy component impact on MR imaging quality for an MRgRT system

Abstract: Radiotherapy components of an magnetic resonnace-guided radiotherapy (MRgRT) system can alter the magnetic fields, causing spatial distortion and image deformation, altering imaging and radiation isocenter coincidence and the accuracy of dose calculations. This work presents a characterization of radiotherapy component impact on MR imaging quality in terms of imaging isocenter variation and spatial integrity changes on a 0.35T MRgRT system, pre-and postupgrade of the system. The impact of gantry position, MLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The geometric distortion and isocenter shift were quantified at multiple gantry angles, additionally, large field of view DVFs were produced to correct the systematic distortions present in acquired MR images. Comparison of isocenter shifts to previous data published by Lewis et al, 18 which used the Fluke spatial integrity phantom, showed good agreement with the maximum isocenter shift of 0.89 mm occurring at gantry angle of 120 • , as it did in this work. The calculated DVF allowed for an independent smaller grid phantom to be corrected back to its original geometry over multiple gantry angles.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The geometric distortion and isocenter shift were quantified at multiple gantry angles, additionally, large field of view DVFs were produced to correct the systematic distortions present in acquired MR images. Comparison of isocenter shifts to previous data published by Lewis et al, 18 which used the Fluke spatial integrity phantom, showed good agreement with the maximum isocenter shift of 0.89 mm occurring at gantry angle of 120 • , as it did in this work. The calculated DVF allowed for an independent smaller grid phantom to be corrected back to its original geometry over multiple gantry angles.…”
Section: Discussionsupporting
confidence: 90%
“…The results in this study closely agree with previous works which used different phantoms and analysis techniques. 16 , 18 This work also found that the on‐board distortion correction was able to correct the geometric distortion to a similar value at all gantry angles, and was a significant improvement over images with the distortion correction turned off. Gantry angle of 0° showed a higher distortion correction value in the AP direction for DstOn scans than other gantry angles, but was the distortion was still corrected by the software.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, image guided radiation therapy (IGRT) can enhance the treatment accuracy. Magnetic resonance guided radiation therapy (MRgRT) based on magnetic resonance imaging (MRI) has been increasingly favored due to the advantage of high soft tissue contrast compared to the conventional IGRT based on X‐ray 2,3 . The advancement of techniques has further complicated the treatment procedures with a potential increase in errors.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance guided radiation therapy (MRgRT) based on magnetic resonance imaging (MRI) has been increasingly favored due to the advantage of high soft tissue contrast compared to the conventional IGRT based on X-ray. 2,3 The advancement of techniques has further complicated the treatment procedures with a potential increase in errors.Thus,the quality assurance (QA) of radiation therapy machine and imaging device is important. The American Association of Physicists in Medicine (AAPM) provides a QA guideline through task group 142 (TG-142).…”
Section: Introductionmentioning
confidence: 99%